EFEKTIVITAS PENGELOLAAN ZAKAT DALAM MENANGGULANGI KEMISKINAN DI KOTA MAKASSAR ( STUDI LAZISMU SUL-SEL ) - yaya, A.Yahyatullah (The Scientia Law and Economics Review, 2023)
ABSTRACT : Effectiveness of Zakat Management in Tackling Poverty in The City of Makassar (Study Lazismu Sul-Sel). The purpose of the study is divided into two, namely practical benefits, namely to know the role of South Sulawesi common steps in tackling poverty in the city of Makassar, to determine the effectiveness of zakat management through Lazismu to Mustahiq. The research method used is descriptive qualitative. Based on the results of the study that the distribution of zakat in tackling poverty in the city of Makassar is very effective in terms of the work guidelines of the South Sulawesi Zakat Lazismu organization such as the organizational structure that regulates the collection and distribution of zakat, the process of observation, assessment, distribution and evaluation, and the existence of a financial audit process. , the process of collection and distribution using a Sharia BANK. With the existence of the Lazismu Amil zakat institution in South Sulawesi, the processing is organized so that it is effective in distributing zakat, especially in tackling poverty in Makassar City